Winter garden - rest for the soul (Journal of Architectural Design, 2022)
The winter garden is a heated room with natural light, designed to accommodate exotic and non-winter-hardy, as well as indoor plants. The winter garden is usually a glazed room with a metal, aluminum, wooden frame or a veranda as a continuation of the living room